Research methods and efficacy of acupuncture in the treatment of Parkinson's disease: a scoping review of systematic reviews and meta-analyses - Yu, Bin; Ma, Shi-qi; Huang, Hai-peng; Zhong, Zhen; Yu, Shuo; Huang, Ke; Zhang, Li-ying; Li, Meng-yuan; Yao, Lin (Frontiers in Neurology, 2023)
Introduction Research on acupuncture for Parkinson's Disease is growing rapidly. A scoping review examines emerging evidence and is important to guide policy and practice. The purpose of this scoping review was to examine the breadth and methodological quality of systematic reviews and meta-analyses, and to map the quality of evidence of these studies to evaluate the efficacy of acupuncture for treatment of PD. Methods Seven literature databases were searched. Two researchers independently screened the literature and extracted relevant information (such as general characteristics, inclusion criteria, study results, and report quality).The inclusion criteria include publicly published systematic reviews/meta-analyses/systematic reviews of acupuncture treatment for Parkinson's disease. The research subjects are any patients who meet the diagnostic criteria for Parkinson's disease, and intervention measures include acupuncture treatment including electro acupuncture, scalp acupuncture, or combination with other treatment methods. The outcome indicators are all types of results related to PD and the effective measurement tools used. Results A total of 23 systematic reviews and/or meta-analyses of studies were included. Most of the articles were published between 2019 and 2023 (47.8%). A total of 14 articles (60.9%) were evaluated and classified, and 89 (36.8.1%) of the 242 included articles were of medium and high quality. Discussion This study comprehensively evaluates the quality and research methods of incorporating SRs/MAs, and concludes that acupuncture treatment for Parkinson's disease may be significant. Considering the shortcomings in research design and methodology, it is not possible to draw conclusions on the evidence of acupuncture treatment for PD at this stage, but it does not mean that acupuncture treatment is ineffective. We hope to focus on improving research design and methods in the study of acupuncture treatment for Parkinson's disease, an increase the credibility of research results.